H2-rich syngas production through mixed residual biomass and HDPE waste via integrated catalytic gasification and tar cracking plus bio-char upgrading - Alipour Moghadam Esfahani, R. (Elsevier B.V., 2017)
Energy recovery via waste utilization in gasification process is an attractive alternative energy source which is expected to supersede part of the energy from fossil fuels. To enhance the H2-rich syngas production from residual biomass mixed with polymeric waste, a dual stage process involving catalytic steam gasification and tar cracking was integrated as a promising alternative technology for clean fuel production. Generally, the presence of tar causes syngas degradation and has been identified as one of the major impurities from the gasification process. This study shows the results obtained from an integrated process with optimization process conditions to enhance H2-rich syngas yield. Nickel and dolomite were used as cheap and effective catalysts in fluidized and fixed bed gasifiers respectively, which resulted in high-quality syngas production with a maximum hydrogen yield of 284.1 gH2 kg−1feedstock and carbon conversion efficiency (CCE) of 92.4 wt. Furthermore, the study eventuates the upgrading of the bio-char to carbon nano-tubes (CNT). In fact CNT could be further employed either in gasification process or as electrocatalyst supporting materials for low-temperature fuel cells. © 2016 Elsevier B.V.